Generalization of the Randall-Sundrum Model Using Gravitational Model F(T,Θ) - S. Davood Sadatian; S. M. Hosseini (Advances in High Energy Physics)
In this letter, we explore a generalized model based on two scenarios including the Randall-Sundrum model and gravity model F(T,Θ). We first study the standard Randall-Sundrum gravitational model and then add a function containing two parameters as torsion and trace energy-momentum tensor to the main action of the model. Next, we derive the equations of the generalized model and obtain a new critical value for the energy density of the brane. The results showed that inflation and the dark energy-dominated stage can be realized in this model. We pointed out one significant category of dark energy models that had greatly developed the knowledge about dark energy. To be specific, dark energy could either be quintessence-like, phantom-like, or the so-called “quintom”-like. The models of quintom type suggest that the equation of state parameter of dark energy can cross the cosmological constant boundary ω=-1. Interestingly, this quintom scenario exactly appeared in this paper.